Effects of inoculum size of afifella marina in the bioprocessing of sargassum spp. meal - Sujjat Al Azad; Mohammad Tamrin Mohamad Lal (Scientific Research Publishing Inc., 2022)
Brown seaweed, Sargassum spp. is also used as an alternative feed ingredient for aquaculture in the form of seaweed meal. Nutritional values seaweed meal with bioprocess technology using microbes such as Lactobacillus , Bacillus or Streptococcus , are improved with different inoculum sizes. Purple non-sulphur bacterium, Afifella marina could be one of the alternative and potential candidates. This study aims to determine the optimum inoculum level and period for the improvement of nutritional values in Sargassum polycystum meal. Sargassum polycystum was collected from the Sepanggar Bay. Dried seaweed was grinded into fine particles (<400 μm). Inoculum sizes of 10% (v/v), 20% (v/v) and 30% (v/v) of A. marina were used with 20 g Sargassum polycystum powder in one liter bottle with autoclaved 112 synthetic media. Bottles were incubated at 2500 lux light intensity at 30˚C ± 1˚C for 8 days. Every two days destructive samples were taken for the determination of nutritional values of bioprocessed seaweed meal. The measured analytical parameters were crude protein (%), crude ash (%), crude fiber (%) and crude lipids (%). Nutritional value of processed seaweed meal powder with A. marina has improved with the increase of inoculum size. The crude protein percentage of 14.70% + 0.40% was significantly high (p < 0.05) with 30% (v/v) inoculum size and obtained on the 8th of bioprocessing product. Consistent decrease in crude fiber values was observed with increase of inoculum sizes, as 19.34% of crude fiber decrement was determined with 30% (v/v) inoculum level on 6th day. The performance of crude lipids was observed insignificant in all inoculum levels. No significant differences (p > 0.05) were observed among the values of crude protein, ash, lipids and fiber within 6th and 8th day. A. mariana with 30% (v/v) inoculum sizes on 6th of day has capability in improving the nutritional values of Sargassum polycystum seaweed meal during bioprocessing.